Greek rebetiko from a psychocultural perspective : same songs changing minds - Koglin, Daniel (SOAS musicology series., 2016)
Greek Rebetiko from a Psychocultural Perspective: Same Songs Changing Minds examines the ways in which audiences in present-day Greece and Turkey perceive and use the Greek popular song genre rebetiko to cultivate specific cultural habits and identities. In the past, rebetiko has been associated chiefly with the lower strata of Greek society. But Daniel Koglin approaches the subject from a different perspective, exploring the mythological and ritual aspects of rebetiko, which intellectual elites on both sides of the Aegean Sea have adapted to their own world views in our age of globalized consumption. Combining qualitative and quantitative methods from ethnomusicology, ritual studies, conceptual history and music psychology, Koglin casts light on the role played by national perceptions in the processes of music production and consumption. His analysis reveals that rebetiko persistently oscillates between conceptual categories: it is a music both 'ours' and 'theirs', marginal and mainstream, joyful and grievous, sacred and profane. The study culminates in the thesis that this semantic multistability is not only a key concept to understanding the ongoing popularity of rebetiko in Greece, and its recent renaissance in Turkey, but also a fundamental aspect of the human experience on the south-eastern borders of Europe.